Baseline Procalcitonin as a Predictor of Bacterial Infection and Clinical Outcomes in Covid-19 - Sheikh Ali Ahmad Ajmal, Syed Faraz Ahmad, Syeda Summiaya Shah, Saud Javed Choudhry, Sara Khan, Imtiaz Nazam (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of our study is to determine either bacterial infection or poor outcomes among patients with Covid-19 caused by increased level of procalcitonin. Study Design: Retrospective/ observational study Place and Duration: THQ Hospital Khairpur Tamewali. Jan 2021-Jun 2021 Methods: In this research, there were a total of 190 patients of both sexes. Patients ranged in age from 20 to 85. Detailed demographics, including age, sex, BMI, residence, and literacy, were obtained from all patients. Association of comorbidities among cases was determined. All the patients diagnosed Covid-19 by nasopharyngeal PCR. Baseline level of procalcitonin was measured among all cases before hospitalization and patients were separated either had bacterial infection or not. Outcomes among all the patients were measured in terms of mortality and survivors. Complete data was examined using the SPSS 23.0 version for statistical purposes alone. Results: Among 190 cases, most of the patients were males 110 (57.9%) and 80 (42.1%) patients were females. Mean age of the patients were 52.13±13.44 years with mean BMI 26.14±11.54 kg/m2. 85 (44.7%) patients were from rural areas and 115 (55.3%) had urban residency. 100 (52.6%) patients were educated. Hypertension was the most common comorbidity found in 120 (63.2%), followed by diabetes 95 (50%), kidney disease found in 40 (21.1%) patients and asthma in 25 (13.2%) patients. Mean PCT among all cases was 1.4±6.13 ng/mL. Bacterial infection (positive blood culture) was found among 130 (68.4%) cases with procalcitonin. Severity of pneumonia was found among 123 cases of bacterial infection. Mortality among all cases were 102 (53.4%) with positive blood culture for bacterial infection. Mean PCT of died patients was 1.1±4.6 ng/mL significantly higher than that of survived patients 2.13±4.45. Blood urea nitrogen and aspartate aminotransferase (AST) were also found a predictive value among died patients. Conclusion: According to our findings, procalcitonin was the only biomarker strongly associated with patient mortality and satisfaction in the intensive care unit. With increasing procalcitonin concentrations, death rates increased as quartiles of procalcitonin levels rose. This study shows that intensivists may use procalcitonin to guide the management of COVID-19 and the utilization of ICU resources.